2000
DOI: 10.1103/physrevd.62.014503
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic universality and the chiral phase transition in two flavor QCD

Abstract: We re-analyze data from available finite-temperature QCD simulations near the chiral transition, with the help of Chiral Random Matrix Theory (chRMT). Statistical properties of the lowest-lying eigenvalues of the staggered Dirac operator for SU(3) lattice gauge theory with dynamical fermions are examined. We consider temperatures below, near, and above the critical temperature Tc for the chiral phase transition. Below and above Tc the statistics are in agreement with the exact analytical predictions in the mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…The properties of the Dirac spectrum have been analyzed in many lattice QCD simulations [ 33,3,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48] [ 49,50,51,52,53,54] and have been found to be in complete agreement with the conclusions of the previous section. We only show three representative examples.…”
Section: Lattice Resultssupporting
confidence: 73%
“…The properties of the Dirac spectrum have been analyzed in many lattice QCD simulations [ 33,3,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48] [ 49,50,51,52,53,54] and have been found to be in complete agreement with the conclusions of the previous section. We only show three representative examples.…”
Section: Lattice Resultssupporting
confidence: 73%
“…[5], partly motivated by the understanding of the fate of U(1) A when SU(N F ) A is restored. The observation that low-lying eigenvalues at T T c neither obey the Airy statistics of the 'soft' band edge of classical random matrices [37,38], nor the statistics of random matrices at the (multi)critical edge [39,40], left open the issue of characterizing these eigenvalues and associated eigenstates.…”
Section: Qcd Dirac Spectra Above T Cmentioning
confidence: 99%
“…Very recently a study of just the low-lying Dirac operator eigenvalues near T c has actually indicated the presence of a gap at large lattice volumes [21]. Again the statistics was rather limited, and only a small number of the lowest-lying eigenvalues could be included (varying between 8 and 10).…”
Section: Introductionmentioning
confidence: 99%
“…The present study will in many ways follow the same lines of thought as Ref. [21], but we shall have much larger statistics, and we shall also probe some different aspects. In particular, we are also interested in seeing whether quenching causes a different behavior of the smallest eigenvalues near T c compared with dynamical fermions.…”
Section: Introductionmentioning
confidence: 99%